"Thiol–ene" click synthesis of chiral covalent organic frameworks for gas chromatography. Issue 37 (2nd September 2021) - Guo, Jing-Xuan; Yang, Cheng; Yan, Xiu-Ping
Abstract : A facile "thiol–ene" click strategy was reported to construct novel chiral COFs for gas chromatographic separation. Abstract : The unique properties of covalent organic frameworks (COFs), such as a large specific surface area, good stability and easy functionalization, make them have good potential in the field of separation science. However, the synthesis of chiral COFs is challenging, so the application of COFs in chiral separation is very limited. Here, we show a simple and effective "thiol–ene" click strategy to construct chiral COFs. The chiral COF CTzDva showed high thermal stability and good porosity, prompting us to explore its application in chromatographic separation. The CTzDva-based gas capillary column showed good separation of benzene/cyclohexane, and racemates (citronellal and fenchone). This work provides a promising platform for the synthesis of chiral COFs and expands the application of COFs in the field of separation.